Developing scientific explanation of grade 11 students through socio-scientific issues learning on respiratory system - Phanchamlong, Kittiphong; Nuangchalerm, Prasart; Sari, Indah Juwita (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This action research aims to develop the scientific explanation ability of grade 11 students to pass the good level up criterion using socio-scientific issues learning in biology on the topic respiratory system. The target group consisted of 17 students in grade 11 students. The research instrument were lesson plans of instrument using socio-scientific issues learning, scientific explanation test, student behavior observation, semi-structure interviews, and student journal. The data were analyzed by descriptive analysis. The results showed in the first cycle, 17 students score did not pass the good level, students received an average scientific explanation score of 3.82 out of a total of 12 points, representing 31.86%. In the second cycle, students received an average scientific explanation score of 7.47 out of a total of 12 points, representing 62.25%, 14 students score did pass the good level, 3 students score did not pass the good level. In the third cycle, students received an average scientific explanation score of 10.82 out of a total of 12 points, representing 90.20%, 17 students score did pass the good level.